Citra Perusahaan dalam Tayangan Acara Televisi Lokal - Donny Perdana de Keizer (Humaniora, 2010)
This paper is about effectiveness imaging event through shows in television local, TVRI Yogyakarta, as government television media main based in Yogyakarta. Limited national budget as TVRI Yogyakarta’s only capital to hold productions in addition to government regulation and limited commercial productions, urges managers to be more creative in creating cooperation chances due to increase income. TVRI, which now as Public Broadcasting Organization, serves public interest with allocated budget by the Nation. Producers’ creativity determines the amount of show sponsors support. There are many ways to maximize its income as a part of imaging in the community. The imaging is not just through advertisement or public service announcement, but also through picture, logo, and sound.